Aluminum plastic film inner layer adhesive, aluminum plastic film and battery
By using a specific inner layer adhesive in aluminum-plastic film, the problem of layering the inner layer and aluminum foil layer at high temperatures is solved, which significantly improves the peel strength and heat seal strength, ensuring the packaging and safety performance of the battery.
Patent Information
- Application Number
- CN202411883824.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-19
- Publication Date
- 2025-03-28
AI Technical Summary
The existing aluminum-plastic film has the problem of layering the inner layer and the aluminum foil layer at high temperatures, resulting in insufficient peel strength and heat seal strength, affecting the packaging and safety performance.
An aluminum-plastic film inner layer adhesive is adopted, including a first polyolefin with a specific melting point and weight average molecular weight and a first curing agent. By defining its mass ratio and preparation method, the adhesive strength and high temperature resistance of the adhesive are improved.
The bonding strength between the aluminum foil layer and the inner layer is significantly improved, the layering phenomenon between the inner layer and the aluminum foil layer is reduced at high temperature, the peel strength and heat seal strength are improved, and the reliable packaging and excellent safety performance of the battery is ensured.
Smart Images

Figure CN119709064A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of battery packaging materials, and in particular to an aluminum-plastic film inner layer adhesive, an aluminum-plastic film and a battery. Background Art
[0002] Aluminum-plastic film is an important material for the soft packaging of lithium-ion batteries, which directly affects the packaging and safety performance of lithium-ion batteries. Traditional aluminum-plastic film materials include an inner layer of polypropylene (CPP) film, an aluminum foil layer and an outer layer stacked in sequence, and the inner layer of CPP film and the aluminum foil layer, as well as the aluminum foil layer and the outer layer are bonded by adhesive. With the advent of the fast charging era, lithium-ion batteries need to be charged with high currents. In a short period of time, the battery will accumulate a large amount of heat, which can easily lead to the delamination of the inner layer of CPP film and the aluminum foil layer. The inner layer cannot meet the higher requirements for peel strength and heat sealing strength, which is not conducive to packaging and safety performance. Therefore, how to improve the peel strength and heat sealing strength of the inner layer of aluminum-plastic film materials at high temperatures is a technical problem that needs to be solved in this field. Summary of the invention
[0003] The main purpose of the present invention is to provide an aluminum-plastic film inner layer adhesive, an aluminum-plastic film and a battery, so as to solve the problem of delamination of the inner layer and the aluminum foil layer of the aluminum-plastic film at high temperature in the prior art.
[0004] In order to achieve the above-mentioned purpose, according to one aspect of the present invention, an aluminum-plastic film inner layer adhesive is provided, which includes a first polyolefin and a first curing agent, the mass ratio of the first polyolefin to the first curing agent is 100:(2-30), the melting point of the first polyolefin is 75-130°C, and the weight average molecular weight is 60,000-150,000.
[0005] Further, the molecular chain of the first polyolefin includes a polyolefin main chain and a modified group grafted on the polyolefin main chain, and the modified group includes at least one of a carboxyl group and an anhydride group; or, the modified group is formed by at least one grafting monomer selected from maleic acid, acrylic acid, itaconic acid, maleic anhydride, and itaconic anhydride;
[0006] Preferably, the polyolefin backbone is a polypropylene-ethylene copolymer polymerized from propylene and ethylene;
[0007] Preferably, based on the total weight of the first polyolefin material being 100%, the polyolefin main chain accounts for 90-99%, and the modified group accounts for 1-10%;
[0008] Preferably, the preparation method of the first polyolefin includes a melt grafting method or a solution grafting method. Preferably, the melt grafting method is to add a grafting monomer containing a modifying group into a twin-screw extruder, and a grafting reaction occurs under the action of a peroxide and an auxiliary agent to obtain the first polyolefin material;
[0009] Preferably, the solution grafting method is to add a grafting monomer containing a modifying group into a solution containing polyolefin, and to cause a grafting reaction under the action of peroxide and an auxiliary agent to obtain a first polyolefin material.
[0010] Furthermore, the first curing agent includes at least one of an epoxy resin curing agent and an isocyanate curing agent;
[0011] Preferably, the isocyanate curing agent includes at least one of diphenylmethane diisocyanate, toluene diisocyanate, and hexamethylene diisocyanate;
[0012] Preferably, the epoxy resin curing agent includes at least one of bisphenol A epoxy resin, novolac epoxy resin and brominated epoxy resin.
[0013] Further, when the first curing agent is an isocyanate curing agent, the mass content of the NCO group in the first curing agent is 18% to 30%, and the mass ratio of the first polyolefin to the first curing agent is 100:(10 to 30); or,
[0014] When the first curing agent is an epoxy resin curing agent, the epoxy equivalent of the first curing agent is 150-250, and the mass ratio of the first polyolefin to the first curing agent is 100:(2-10).
[0015] The second aspect of the present invention provides an aluminum-plastic film, which includes an inner layer, a first adhesive layer, an aluminum foil layer, a second adhesive layer and an outer layer stacked in sequence; wherein the material forming the first adhesive layer is the aluminum-plastic film inner layer adhesive provided in the first aspect.
[0016] Furthermore, the outer layer includes an inner layer, an intermediate layer and a surface layer which are sequentially stacked along an extending direction from the inner layer to the first adhesive layer;
[0017] Wherein, the material forming the surface layer comprises, by weight: 100 parts of polycaprolactam and 5 to 20 parts of polyhexamethylene adipamide; preferably, the melting point of polycaprolactam is 220 to 225° C., and the melting point of polyhexamethylene adipamide is 250 to 260° C.; and / or,
[0018] The materials forming the surface layer include, by weight: 100 parts of polycaprolactam and 0.5 to 1.5 parts of silicon dioxide; and / or,
[0019] The surface of the surface layer is provided with an inorganic coating, and the material forming the inorganic coating includes at least one of aluminide and ceramic.
[0020] Further, the material forming the second adhesive layer includes polyester resin and a second curing agent; and / or,
[0021] Materials forming the inner layer include polypropylene;
[0022] The material forming the inner layer is polyamide;
[0023] Preferably, the polyamide is at least one selected from polycaprolactam, polyhexamethylene adipamide, polylaurolactam, polydecanediamine sebacate, and a copolymer of polycaprolactam and polyhexamethylene adipamide;
[0024] Preferably, the polyamide is at least one selected from polycaprolactam, polyhexamethylene adipamide, polylaurolactam, polydecanediamine sebacate, and a copolymer of polycaprolactam and polyhexamethylene adipamide;
[0025] The material forming the middle layer includes at least one of polyester resin and polyamide resin. Preferably, the polyester resin is selected from at least one of polyethylene terephthalate, polybutylene terephthalate, polyethylene naphthalate, polybutylene naphthalate and polyethylene isophthalate. The polyamide resin is selected from at least one of polycaprolactam, polyhexamethylene adipamide, polylaurolactam, polydecamethylenediamine and a copolymer of polycaprolactam and polyhexamethylene adipamide.
[0026] Preferably, the second curing agent includes at least one of an aliphatic polyisocyanate and an aromatic isocyanate;
[0027] Preferably, the aliphatic polyisocyanate is selected from at least one of HDI hexamethylene 1,6 diisocyanate trimer and IPDI isophorone diisocyanate; the aromatic isocyanate is selected from at least one of MDI diphenylmethane diisocyanate and TDI toluene diisocyanate.
[0028] Further, the thickness of the aluminum-plastic film is 100-200 μm; and / or,
[0029] The thickness ratio of the inner layer, the first adhesive layer, the aluminum foil layer, the second adhesive layer, and the outer layer is (1-30): (40-98): (1-30); and / or,
[0030] Preferably, the thickness ratio of the inner layer, the middle layer and the surface layer is (5-20): (60-90): (5-20);
[0031] Preferably, the thickness of the inorganic coating is 1 to 10 μm;
[0032] Preferably, the thickness of the first adhesive layer and the second adhesive layer are both 2-5 μm.
[0033] Furthermore, in the aluminum-plastic film, the peel strength of the inner layer (1) at 120° C. is ≥2.5N / 15mm, and the heat sealing strength at 80° C. is ≥30N / 15mm.
[0034] A third aspect of the present invention provides a battery, comprising a battery cell and the aluminum-plastic film provided in the second aspect, wherein the aluminum-plastic film is used to encapsulate the battery cell.
[0035] By applying the technical solution of the present invention, by introducing a first polyolefin with a specific melting point and a specific weight-average molecular weight, and limiting the mass ratio of the first polyolefin to the first curing agent, the bonding strength of the adhesive can be significantly improved, ensuring that it has good high temperature resistance. When applied to an aluminum-plastic film, a strong bond can be formed between the aluminum foil layer and the inner layer, reducing the delamination phenomenon between the inner layer and the aluminum foil layer at high temperatures, and significantly improving the peel strength and heat sealing strength of the inner layer at high temperatures, so that the battery encapsulated by the aluminum-plastic film has reliable encapsulation and excellent safety performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] Figure 1 This is a schematic diagram of the structure of an aluminum-plastic film in one embodiment of the present invention;
[0037] Figure 2 Schematic diagram of the structure of an aluminum-plastic film in another embodiment of the present invention.
[0038] Description of reference numerals:
[0039] 1-inner layer; 2-first adhesive layer; 3-aluminum foil layer; 4-second adhesive layer; 5-outer layer; 51-inner layer; 52-middle layer; 53-surface layer; 6-inorganic coating. DETAILED DESCRIPTION
[0040] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.
[0041] As described in the background of the present invention, in the prior art, the aluminum-plastic film has the problem of delamination of the inner layer 1 and the aluminum foil layer 3 at high temperature. In order to solve the above problem, the first aspect of the present invention provides an aluminum-plastic film inner layer adhesive, characterized in that the aluminum-plastic film inner layer adhesive comprises a first polyolefin and a first curing agent, the mass ratio of the first polyolefin to the first curing agent is 100: (2-30), the melting point of the first polyolefin is 75-130°C, and the weight average molecular weight is 60,000-150,000.
[0042] The inner layer adhesive of the aluminum-plastic film of the present invention can be used as the adhesive layer material between the inner layer 1 and the aluminum foil layer 3 to make the inner layer 1 and the aluminum foil layer 3 closely adhere to each other. The inner layer adhesive of the aluminum-plastic film includes a first polyolefin and a first curing agent.
[0043] Specifically, the first polyolefin is a copolymer formed by polymerization of olefin monomers such as ethylene and propylene. The melting point and molecular weight of the polyolefin have a certain influence on the peel strength and heat seal strength of the adhesive. Specifically, the higher the melting point of the polyolefin, the higher the molecular weight, the longer the molecular chain, the stronger the interaction force between the molecular chains, and the higher the degree of entanglement between the molecular chains, thereby increasing the peel strength of the material; the higher the melting point of the polyolefin, the higher its melting temperature during the heat sealing process, which helps to improve the heat sealing strength; the higher the molecular weight of the polyolefin, the better the melt fluidity, which helps to form a uniform molten layer during the heat sealing process, thereby improving the heat sealing strength. At the same time, polyolefins with higher molecular weights usually have higher crystallinity, which helps to improve the crystallinity at the heat seal and enhance the heat sealing strength. However, too high a melting point and too high a molecular weight may lead to a larger melt viscosity in practical applications, making it difficult to process, increasing energy consumption during the heat sealing process, and affecting production efficiency; and when the molecular weight increases to a certain extent, it may cause the material to be too hard and the peel strength to decrease.
[0044] The present invention limits the melting point of the first polyolefin to 75-130°C and the weight average molecular weight to 60,000-150,000. This indicates that the interaction force between the molecular chains of the first polyolefin is strong, the degree of entanglement between the molecular chains is also high, the melting temperature during the heat sealing process is higher, and the crystallinity at the heat sealing portion is high, thereby improving the bonding strength of the inner layer adhesive of the aluminum-plastic film, ensuring that it has good high temperature resistance, and applying it to the aluminum-plastic film can form a strong bond between the aluminum foil layer 3 and the inner layer 1, reduce the delamination phenomenon between the inner layer 1 and the aluminum foil layer 3 at high temperatures, and significantly improve the peel strength and heat sealing strength of the inner layer 1 at high temperatures. At the same time, by limiting the melting point and molecular weight within an appropriate range, the processability of the inner layer adhesive of the aluminum-plastic film can be taken into account.
[0045] The first curing agent plays an important role in the inner layer adhesive of the aluminum-plastic film. Its main function is to promote the transition of the adhesive from a liquid or semi-solid state to a solid state, thereby achieving bonding. Specifically, the first curing agent reacts chemically with the first polyolefin or other components to change the adhesive from a liquid or semi-solid state to a solid state. This reaction is usually called a polymerization reaction or a cross-linking reaction. In addition, the first curing agent can shorten the time it takes for the adhesive to change from a liquid or semi-solid state to a solid state, which makes the adhesive more efficient during the bonding process, improves the curing efficiency of the adhesive, shortens the production cycle, and reduces costs.
[0046] By limiting the mass ratio of the first polyolefin to the first curing agent to 100:(2-30), the bonding strength, high temperature resistance and curing efficiency of the inner layer adhesive of the aluminum-plastic film can be improved. The mass ratio of the first polyolefin to the first curing agent is 100:(2-30), for example, 100:2, 100:5, 100:10, 100:15, 100:20, 100:25, 100:30 or a range consisting of any two of them.
[0047] The present invention does not limit the specific type of the first polyolefin, which can be a copolymer formed by polymerization of one, two or more olefin monomers, or a modified copolymer. In order to improve the performance of polyolefins or give them new functions, it can be achieved through grafting modification. For example, in some embodiments, the molecular chain of the first polyolefin includes a polyolefin main chain and a modified group grafted on the polyolefin main chain, and the modified group includes at least one of a carboxyl group and an anhydride group; or, the modified group is formed by at least one grafted monomer selected from maleic acid, acrylic acid, itaconic acid, maleic anhydride, and itaconic anhydride. In some embodiments, the polyolefin main chain is a polypropylene-ethylene copolymer formed by polymerization of propylene and ethylene.
[0048] In some preferred embodiments, based on the total weight of the first polyolefin material being 100%, the proportion of the polyolefin main chain is 90% to 99%, and the proportion of the modified group is 1% to 10%. By adjusting the proportion of the polyolefin main chain and the modified group, the formation of the first polyolefin with different melting points and molecular weights can be achieved.
[0049] Graft modification refers to the introduction of modified groups on the polyolefin main chain to change its original physical and chemical properties. These modified groups can be introduced on the polyolefin main chain through chemical reactions, or by initiating free radical reactions on the polyolefin main chain using high-energy radiation (such as gamma rays or electron beams) to introduce modified groups, or by mixing the modified groups with the polyolefin main chain under the action of mechanical force to achieve grafting through physical action.
[0050] In some preferred embodiments, the preparation method of the first polyolefin includes a melt grafting method or a solution grafting method. Preferably, the melt grafting method is to add a grafting monomer containing a modified group into a twin-screw extruder, and a grafting reaction occurs under the action of peroxide and an auxiliary agent to obtain a first polyolefin material; the solution grafting method is to add a grafting monomer containing a modified group into a solution containing polyolefin, and a grafting reaction occurs under the action of peroxide and an auxiliary agent to obtain a first polyolefin material. The solution containing polyolefin is a non-polar solvent in which polyolefin is dissolved, wherein the peroxide can be at least one of dibenzoyl peroxide, diisopropylbenzene peroxide, and peroxydicarbonate, and these peroxides have high activity and are conducive to the grafting reaction. The auxiliary agent can be an azo compound, an organic tin compound, an organic boron compound (such as triphenylboron), and an organic copper compound (such as divalent copper acetate). Such compounds can be used as auxiliary agents to improve the efficiency of the grafting reaction.
[0051] The present invention does not limit the specific type of the first curing agent, which can be a conventional curing agent in the art. For example, in some embodiments, the first curing agent includes at least one of an epoxy resin curing agent and an isocyanate curing agent. Specifically, the isocyanate curing agent includes at least one of diphenylmethane diisocyanate (MDI), toluene diisocyanate (TDI), and hexamethylene diisocyanate (HDI), preferably HDI with a high functional group content; the epoxy resin curing agent includes at least one of bisphenol A epoxy resin, novolac epoxy resin, and brominated epoxy resin, preferably novolac epoxy resin, which has more than 2 epoxy groups compared to bisphenol A epoxy resin, has a higher curing density, and has a better thermal stability of the aromatic ring, thereby further improving the high temperature resistance of the adhesive layer formed by the inner layer adhesive of the aluminum-plastic film.
[0052] In order to further improve the thermal stability of the inner layer adhesive of the aluminum-plastic film, improve the peel strength and heat sealing strength of the inner layer at high temperature. In one embodiment, when the first curing agent is an isocyanate curing agent, the mass content of the NCO group in the first curing agent is 18% to 30%, and the mass ratio of the first polyolefin to the first curing agent is 100: (10 to 30). By limiting the curing system with a high NCO group content, a large amount or even an excessive amount of NCO groups reacts with the modified groups in the first polyolefin to form a polyimide bond with high temperature resistance, thereby further improving the high temperature resistance of the adhesive layer formed by the inner layer adhesive of the aluminum-plastic film. In another embodiment, when the first curing agent is an epoxy resin curing agent, the epoxy equivalent of the first curing agent is 150 to 250, and the mass ratio of the first polyolefin to the first curing agent is 100: (2 to 10). By limiting the curing system with a high epoxy equivalent, a large amount or even an excessive amount of epoxy groups reacts with the first polyolefin, thereby further improving the high temperature resistance of the adhesive layer formed by the inner layer adhesive of the aluminum-plastic film.
[0053] Specifically, the first curing agent is an isocyanate curing agent, the mass ratio of the first polyolefin to the first curing agent is 100: (10-30), such as 100: 10, 100: 15, 100: 20, 100: 25, 100: 30 or any two thereof, and the mass content of the NCO group in the first curing agent is 18% to 30%, such as 18%, 20%, 24%, 25%, 28%, 30% or any two thereof. When the first curing agent is an epoxy resin curing agent, the mass ratio of the first polyolefin to the first curing agent is 100: (2-10), such as 100: 2, 100: 4, 100: 5, 100: 8, 100: 10 or any two thereof, and the epoxy equivalent of the first curing agent is 150-250, such as 150, 180, 200, 220, 250 or any two thereof.
[0054] like Figure 1 and Figure 2 As shown, the second aspect of the present invention provides an aluminum-plastic film, which includes an inner layer 1, a first adhesive layer 2, an aluminum foil layer 3, a second adhesive layer 4 and an outer layer 5 stacked in sequence; wherein the material forming the first adhesive layer 2 is the aluminum-plastic film inner layer adhesive provided in the first aspect.
[0055] Specifically, the first adhesive layer 2 is used to bond the inner layer 1 and the aluminum foil layer 3, and the second adhesive layer 4 is used to bond the aluminum foil layer 3 and the outer layer 5. Since the material forming the first adhesive layer 2 is the aluminum-plastic film inner layer adhesive with high bonding strength and excellent high temperature resistance, a strong bond is formed between the inner layer 1 and the aluminum foil layer 3, reducing the delamination phenomenon between the inner layer 1 and the aluminum foil layer 3 at high temperatures, and significantly improving the peel strength and heat sealing strength of the inner layer 1 at high temperatures.
[0056] In the specific implementation process of the present invention, the inner layer 1 is bonded to one surface of the aluminum foil layer 3 under the action of the first adhesive layer 2, and the inner layer 1 serves as the inner surface of the aluminum-plastic film. After packaging, the inner layer 1 will contact the electrolyte and the battery cell; the outer layer 5 is bonded to the other surface of the aluminum foil layer 3 under the action of the second adhesive layer 4, and the outer layer 5 serves as the outer surface of the aluminum-plastic film. After packaging, it will contact the outside air.
[0057] At present, in order to improve production efficiency and quality consistency, most of them are achieved by increasing the heat sealing temperature, which will cause the outer layer 5 to have poor appearance such as wrinkling, blistering, stickiness, and delamination. In order to further improve the high temperature resistance of the aluminum-plastic film without reducing the toughness of the aluminum-plastic film while taking into account the appearance of the outer layer 5. In some embodiments, the outer layer 5 can be set as a three-layer structure, for example, the outer layer 5 includes an inner layer 51, an intermediate layer 52 and a surface layer 53 stacked in sequence along the extension direction from the inner layer 1 to the first adhesive layer 2; wherein, by modifying the outer layer 5, under the synergistic effect of the first adhesive layer 2 and the outer layer 5, the high temperature resistance and toughness of the aluminum-plastic film can be further improved, so that it can ensure the delamination of the inner layer 1 and the aluminum foil layer 3 at high temperature, and reduce the poor appearance of the outer layer 5.
[0058] Specifically, in some embodiments, the material forming the surface layer 53 includes, by weight, 100 parts of polycaprolactam and 5 to 20 parts of polyhexamethylene adipamide. In some preferred embodiments, the melting point of polycaprolactam (PA6) is 220 to 225° C., and the melting point of polyhexamethylene adipamide (PA66) is 250 to 260° C. By introducing high melting point PA66, the high temperature resistance of the aluminum-plastic film can be further improved without reducing the toughness of the aluminum-plastic film.
[0059] In other embodiments, the material forming the surface layer 53 includes, by weight, 100 parts of polycaprolactam and 0.5 to 1.5 parts of silicon dioxide. Silicon dioxide is an inorganic compound with high hardness and good thermal stability. By introducing silicon dioxide, the wear of the aluminum-plastic film during processing and use can be reduced, and the high temperature resistance of the aluminum-plastic film can be improved to a certain extent.
[0060] like Figure 2 As shown, the outer layer 5 of the present invention can also be a four-layer structure. In some embodiments, the surface of the surface layer 53 is provided with an inorganic coating 6, and the material forming the inorganic coating 6 includes at least one of aluminide and ceramic. By providing a high-temperature resistant coating on the surface of the outer layer 5, the high-temperature resistance of the aluminum-plastic film can be further improved.
[0061] The present invention does not limit the specific materials of the other layers except the first adhesive layer 2 and the outer layer 5, which may be conventional materials in the art. For example, in some embodiments, the material forming the second adhesive layer 4 may include polyester resin and a second curing agent; the material forming the inner layer 1 may include polypropylene, and the material forming the inner layer 51 may include polyamide, such as aliphatic polyamides including polycaprolactam (nylon 6), polyhexamethylene adipamide (nylon 66), polylaurolactam (nylon 12), polydecanediamide (nylon 610), copolymers of nylon 6 and nylon 66, and may be a blend of one or more of them. ); the material forming the middle layer 52 may include at least one of a polyester resin and a polyamide resin. Preferably, the polyester resin is selected from at least one of polyethylene terephthalate, polybutylene terephthalate, polyethylene naphthalate, polybutylene naphthalate, and polyethylene isophthalate; and the polyamide resin is selected from at least one of polycaprolactam (nylon 6), polyhexamethylene adipamide (nylon 66), polylaurolactam (nylon 12), polydecanediamine (nylon 610), and a copolymer of nylon 6 and nylon 66.
[0062] The second curing agent includes at least one of aliphatic polyisocyanate and aromatic isocyanate; for example, the aliphatic polyisocyanate is selected from at least one of HDI hexamethylene 1,6 diisocyanate trimer and IPDI isophorone diisocyanate; the aromatic isocyanate is selected from at least one of MDI diphenylmethane diisocyanate and TDI toluene diisocyanate.
[0063] The present invention does not limit the thickness of each layer, and can be adjusted according to actual conditions. In some embodiments, the thickness of the aluminum-plastic film is 100-200 μm; the thickness ratio of the inner layer 1, the aluminum foil layer 3, and the outer layer 5 is (1-30): (40-98): (1-30); preferably, the thickness ratio of the inner layer 51, the middle layer 52, and the surface layer 53 is (5-20): (60-90): (5-20); preferably, the thickness of the inorganic coating 6 is 1-10 μm; the thickness of the first adhesive layer 2 and the second adhesive layer 4 are both 2-5 μm.
[0064] In the aluminum-plastic film of the present invention, the peel strength of the inner layer 1 at 120° C. is ≥2.5N / 15mm, and the heat-sealing strength at 80° C. is ≥30N / 15mm.
[0065] A third aspect of the present invention provides a battery, comprising a battery cell and the aluminum-plastic film provided in the second aspect, wherein the aluminum-plastic film is used to encapsulate the battery cell.
[0066] The aluminum-plastic film of the present invention is mainly used for lithium batteries. Specifically, the battery cell of the present invention can be a lithium battery cell. After the aluminum-plastic film is packaged, the inner layer 1 of the aluminum-plastic film is tightly attached to the battery cell. Since it includes the aluminum-plastic film with excellent performance, the battery of the present invention has excellent safety performance and good packaging.
[0067] The present application is further described in detail below in conjunction with specific embodiments. These embodiments should not be construed as limiting the scope of protection claimed in the present application.
[0068] Example 1
[0069] The inner layer adhesive of the aluminum-plastic film of this embodiment includes the following components: a first polyolefin (maleic acid-modified polypropylene resin) and a first curing agent (phenolic epoxy resin), wherein the mass ratio of the first polyolefin to the first curing agent is 100:10; wherein the melting point of the first polyolefin is 75° C. and the weight average molecular weight is 60,000;
[0070] The preparation method of the first polyolefin includes: adding maleic acid to a solution containing polypropylene-ethylene resin, and causing a grafting reaction under the action of dibenzoyl peroxide and triphenylboron to obtain the first polyolefin, wherein the mass proportion of the polyolefin main chain is 97%, the modified group is a carboxyl group, and the mass proportion is 3%, and the first curing agent is a phenolic epoxy resin, and the epoxy equivalent is 100.
[0071] 2. Preparation of aluminum-plastic film
[0072] Aluminum foil with a thickness of 40 μm is selected as the aluminum foil layer 3;
[0073] The inner layer adhesive of the aluminum-plastic film is coated on one surface of the aluminum-plastic film at a temperature of 110° C. to form a first adhesive layer of 3 μm, and then a 30 μm inner layer is laminated; the second adhesive layer slurry is coated on the other surface of the aluminum foil layer 3 to form a second adhesive layer of 3 μm, and then a 30 μm outer layer film is laminated, and after aging at a temperature of 60° C. for 5 days, the aluminum-plastic film of this embodiment is obtained;
[0074] The outer layer is a three-layer structure and is made of a film formed by biaxial stretching of polycaprolactam, wherein 2% PA66 and 0.5% silica are added to the surface layer.
[0075] Example 2
[0076] The difference from Example 1 is that the melting point of the first polyolefin is 100° C. by adjusting the preparation parameters.
[0077] Example 3
[0078] The difference from Example 1 is that the melting point of the first polyolefin is 130° C. by adjusting the preparation parameters.
[0079] Example 4
[0080] The difference from Example 1 is that the weight average molecular weight of the first polyolefin is 100,000 by adjusting the preparation parameters.
[0081] Example 5
[0082] The difference from Example 1 is that the weight average molecular weight of the first polyolefin is 150,000 by adjusting the preparation parameters.
[0083] Example 6
[0084] The difference from Example 1 is that no PA66 is added to the surface layer.
[0085] Example 7
[0086] The difference from Example 1 is that no silicon dioxide is added to the surface layer.
[0087] Example 8
[0088] The difference from Example 1 is that the mass ratio of the first polyolefin to the first curing agent is 100:2.
[0089] Example 9
[0090] The difference from Example 1 is that the mass ratio of the first polyolefin to the first curing agent is 100:30.
[0091] Example 10
[0092] The difference from Example 1 is that by adjusting the preparation parameters, based on the total weight of the first polyolefin material being 100%, the proportion of the polyolefin main chain is 99%, and the mass proportion of the modified group carboxyl is 1%.
[0093] Embodiment 11
[0094] The difference from Example 1 is that by adjusting the preparation parameters, based on the total weight of the first polyolefin material being 100%, the polyolefin main chain accounts for 90% and the modified group carboxyl accounts for 10%.
[0095] Example 12
[0096] The difference from Example 1 is that the first curing agent is a phenolic epoxy resin with an epoxy equivalent of 150.
[0097] Example 13
[0098] The difference from Example 1 is that the first curing agent is a phenolic epoxy resin with an epoxy equivalent of 200.
[0099] Embodiment 14
[0100] The difference from Example 1 is that the first curing agent is a phenolic epoxy resin with an epoxy equivalent of 250.
[0101] Embodiment 15
[0102] The difference from Example 1 is that the first curing agent is an isocyanate curing agent, wherein the mass content of NCO groups is 15%.
[0103] Example 16
[0104] The difference from Example 1 is that the first curing agent is an isocyanate curing agent, in which the mass content of NCO groups is 18%.
[0105] Embodiment 17
[0106] The difference from Example 1 is that the first curing agent is an isocyanate curing agent, in which the mass content of NCO groups is 25%.
[0107] Embodiment 18
[0108] The difference from Example 1 is that the first curing agent is an isocyanate curing agent, in which the mass content of NCO groups is 30%.
[0109] Comparative Example 1
[0110] The difference from Example 1 is that the melting point of the first polyolefin is 60° C. by adjusting the preparation parameters.
[0111] Comparative Example 2
[0112] The difference from Example 1 is that the melting point of the first polyolefin is 140° C. by adjusting the preparation parameters.
[0113] Comparative Example 3
[0114] The difference from Example 1 is that the weight average molecular weight of the first polyolefin is 50,000 by adjusting the preparation parameters.
[0115] Comparative Example 4
[0116] The difference from Example 1 is that the weight average molecular weight of the first polyolefin is 200,000 by adjusting the preparation parameters.
[0117] Comparative Example 5
[0118] The difference from Example 1 is that the mass ratio of the first polyolefin to the first curing agent is 100:5.
[0119] Comparative Example 6
[0120] The difference from Example 1 is that the mass ratio of the first polyolefin to the first curing agent is 100:40.
[0121] Test example
[0122] 1. Peel strength at high temperature
[0123] The aluminum-plastic film was cut into 15mm (TD)*100mm (MD) specimens, and the peel strength between the inner CPP layer and the aluminum foil layer at 120°C was tested using a universal testing machine. The test method was T-type peeling, and the tensile rate was 100mm / min.
[0124] 2. Heat sealing strength at high temperature
[0125] The aluminum-plastic film was cut into 60mm (TD) * 100mm (MD) strips, folded in half along the MD direction, and side-sealed using a heat sealer. The copper seal width was 4mm. The heat sealing conditions were: 180°C, 0.3MPa, 3s. The heat-sealed samples were cut into 15mm (TD) * 50mm (MD) strips. The heat sealing strength at 80°C was tested using a universal testing machine. The test method was T-type test, and the tensile rate was 300mm / min.
[0126] 3. Surface appearance
[0127] The aluminum-plastic film was cut into strips of 60 mm (TD) * 100 mm (MD), folded in half along the MD direction, and side-sealed using a heat sealer. The width of the copper seal strip was 4 mm. The heat sealing conditions were: 195°C, 0.4 MPa, 3 s. The heat-sealed area of the sample was observed for abnormalities. Slight whitening of the surface was marked as √, and obvious whitening or slight adhesion of the heat-sealed copper strip to the surface was marked as ×.
[0128] The test results are shown in Table 1.
[0129] Table 1
[0130]
[0131]
[0132] By comparing Examples 1 to 7 and Comparative Examples 1 to 4, it can be seen that Examples 1 to 7 satisfy the requirement that the melting point of the first polyolefin is 75 to 130°C and the weight average molecular weight is 60,000 to 150,000, while Comparative Examples 1 to 2 do not satisfy the requirement that the melting point of the first polyolefin is 75 to 130°C, and Comparative Examples 3 to 4 do not satisfy the requirement that the weight average molecular weight of the first polyolefin is 60,000 to 150,000. The peel strength of the inner layer of Examples 1 to 7 at 120°C and the heat seal strength at 80°C are much higher than those of Comparative Examples 1 to 4. It can be seen that the present invention can significantly improve the heat seal strength and peel strength by limiting the melting point of the first polyolefin to 75 to 130°C and the weight average molecular weight to 60,000 to 150,000, thereby avoiding the problem of delamination of the inner layer and the aluminum foil layer of the aluminum-plastic film at high temperatures.
[0133] Furthermore, compared with Examples 6 to 7, Examples 1 to 5 further meet the requirements of introducing PA66 and silica into the surface layer on the basis of satisfying the melting point of the first polyolefin of 75 to 130°C and the weight average molecular weight of 60,000 to 150,000, which can further improve the peel strength and heat sealing strength, and specifically can achieve the peel strength of the inner layer at 120°C ≥ 2.5N / 15mm, and the heat sealing strength at 80°C ≥ 30N / 15mm. In addition, the temperature resistance of the aluminum-plastic film can be further improved, and the nylon layer will not whiten when heat-sealed at higher temperatures and pressures, thereby avoiding affecting the later wet heat weathering resistance.
[0134] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. An aluminum-plastic film inner layer adhesive, characterized in that: The inner layer adhesive of the aluminum-plastic film comprises a first polyolefin and a first curing agent, wherein the mass ratio of the first polyolefin to the first curing agent is 100:(2-30), the melting point of the first polyolefin is 75-130° C., and the weight average molecular weight is 60,000-150,000.
2. The aluminum-plastic film inner layer adhesive according to claim 1, characterized in that: The molecular chain of the first polyolefin includes a polyolefin main chain and a modified group grafted onto the polyolefin main chain, wherein the modified group includes at least one of a carboxyl group and an acid anhydride group; or, the modified group is formed by at least one grafting monomer selected from the group consisting of maleic acid, acrylic acid, itaconic acid, maleic anhydride and itaconic anhydride; Preferably, the polyolefin backbone is a polypropylene-ethylene copolymer formed by polymerization of propylene and ethylene; Preferably, based on the total weight of the first polyolefin material being 100%, the polyolefin main chain accounts for 90-99%, and the modified group accounts for 1-10%; Preferably, the preparation method of the first polyolefin comprises a melt grafting method or a solution grafting method. Preferably, the melt grafting method is to add a grafting monomer containing a modified group into a twin-screw extruder, and a grafting reaction occurs under the action of a peroxide and an auxiliary agent to obtain the first polyolefin material; Preferably, the solution grafting method is to add a grafting monomer containing a modifying group into a solution containing polyolefin, and to cause a grafting reaction under the action of peroxide and an auxiliary agent to obtain the first polyolefin material.
3. The aluminum-plastic film inner layer adhesive according to claim 1 or 2, characterized in that: The first curing agent includes at least one of an epoxy resin curing agent and an isocyanate curing agent; Preferably, the isocyanate curing agent includes at least one of diphenylmethane diisocyanate, toluene diisocyanate, and hexamethylene diisocyanate; Preferably, the epoxy resin curing agent includes at least one of bisphenol A epoxy resin, novolac epoxy resin and brominated epoxy resin.
4. The aluminum-plastic film inner layer adhesive according to claim 3, characterized in that: When the first curing agent is an isocyanate curing agent, the mass content of NCO groups in the first curing agent is 18% to 30%, and the mass ratio of the first polyolefin to the first curing agent is 100:(10 to 30); or, When the first curing agent is an epoxy resin curing agent, the epoxy equivalent of the first curing agent is 150-250, and the mass ratio of the first polyolefin to the first curing agent is 100:(2-10).
5. An aluminum-plastic film, characterized in that: The aluminum-plastic film comprises an inner layer (1), a first adhesive layer (2), an aluminum foil layer (3), a second adhesive layer (4) and an outer layer (5) which are stacked in sequence; wherein the material forming the first adhesive layer (2) is the aluminum-plastic film inner layer adhesive according to any one of claims 1 to 4.
6. The aluminum-plastic film according to claim 5, characterized in that: The outer layer (5) comprises an inner layer (51), an intermediate layer (52) and a surface layer (53) which are stacked in sequence along the extending direction from the inner layer (1) to the first adhesive layer (2); Wherein, the material forming the surface layer (53) comprises, by weight: 100 parts of polycaprolactam and 5-20 parts of polyhexamethylene adipamide; preferably, the melting point of the polycaprolactam is 220-225° C., and the melting point of the polyhexamethylene adipamide is 250-260° C.; and / or, The material forming the surface layer (53) comprises, by weight: 100 parts of polycaprolactam and 0.5 to 1.5 parts of silicon dioxide; and / or, The surface of the surface layer (53) is provided with an inorganic coating (6), and the material forming the inorganic coating (6) includes at least one of aluminide and ceramic.
7. The aluminum-plastic film according to claim 6, characterized in that: The material forming the second adhesive layer (4) includes polyester resin and a second curing agent; and / or, The material forming the inner layer (1) comprises polypropylene; The material forming the inner layer (51) is polyamide; Preferably, the polyamide is at least one selected from polycaprolactam, polyhexamethylene adipamide, polylaurolactam, polydecanediamine sebacate, and a copolymer of polycaprolactam and polyhexamethylene adipamide; The material forming the intermediate layer (52) includes at least one of a polyester resin and a polyamide resin. Preferably, the polyester resin is selected from at least one of polyethylene terephthalate, polybutylene terephthalate, polyethylene naphthalate, polybutylene naphthalate, and polyethylene isophthalate. The polyamide resin is selected from at least one of polycaprolactam, polyhexamethylene adipamide, polylaurolactam, polydecamethylenediamine, and a copolymer of polycaprolactam and polyhexamethyleneadipamide. Preferably, the second curing agent includes at least one of aliphatic polyisocyanate and aromatic isocyanate; Preferably, the aliphatic polyisocyanate is selected from at least one of HDI hexamethylene 1,6 diisocyanate trimer and IPDI isophorone diisocyanate; the aromatic isocyanate is selected from at least one of MDI diphenylmethane diisocyanate and TDI toluene diisocyanate.
8. The aluminum-plastic film according to claim 6, characterized in that: The thickness of the aluminum-plastic film is 100-200 μm; and / or, The thickness ratio of the inner layer (1), the aluminum foil layer (3), and the outer layer (5) is (1-30): (40-98): (1-30); and / or, Preferably, the thickness ratio of the inner layer (51), the middle layer (52) and the surface layer (53) is (5-20): (60~90):(5~20); Preferably, the thickness of the inorganic coating (6) is 1 to 10 μm; Preferably, the thickness of the first adhesive layer (2) and the second adhesive layer (4) are both 2-5 μm.
9. The aluminum-plastic film according to any one of claims 5 to 8, characterized in that: In the aluminum-plastic film, the peel strength of the inner layer (1) at 120° C. is ≥2.5N / 15mm, and the heat sealing strength at 80° C. is ≥30N / 15mm.
10. A battery, characterized in that: The invention comprises a battery core and the aluminum-plastic film according to any one of claims 5 to 9, wherein the aluminum-plastic film is used for encapsulating the battery core.